The Influence of Professionalism, Internal Control System, and Internal Audit on Good Corporate Governance Implementation (International Forum of Researchers and Lecturers, 2025)
Good Corporate Governance (GCG) is a form of decision by placing the company to be more organized and structured, according on the principles of transparency, independence, responsibility, accountability, also fairness. This study goal to determine the effect of professionalism, internal control systems, also internal audits on the implementation of GCG. This study uses a quantitative research type. The population comprised of 156 individuals is the personnel of the Administration & Commercial Division, Engineering Division, and Operational Division at PT Angkasa Pura Indonesia, Supadio Airport Branch, which are involved in the implementation of GCG. Utilizing the Slovin formula and data collection techniques, the sampling technique is purposive and non-probability, with a total of 115 respondents receiving questionnaires. Validity, reliability, classical assumption tests, multiple linear regression analysis, t-test, also coefficient of determination were used in this study to facilitate data processing, assisted by IBM SPSS version 25. The study findings indicate that professionalism, internal control systems, also internal audits on the implementation of GCG. Partially, the professionalism has a significant positive impact on the implementation of GCG, can be seen from the sig value 0.007 < 0.05, the internal control system has a significant positive impact on the implementation of GCG, can be seen from the sig value 0.000 < 0.05, and internal audit has a significant positive impact on the implementation of GCG, can be seen from the sig value 0.000 < 0.05.